2012
DOI: 10.1080/09593330.2011.627882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenol and acetate addition on 2-chlorophenol consumption by a denitrifying sludge

Abstract: Chlorophenols are widely distributed in the environment. Various strategies have been used to improve their biological elimination under anaerobic conditions; however, such information is still scarce. The aim of this study was to evaluate in batch assays the consumption of 2-chlorophenol (2-CP) by a denitrifying sludge and the influence of acetate or phenol as co-substrates in the 2-CP consumption. It was observed that phenol (69 and 92 mg phenol-C L(-1)) and acetate (60 and 108 mg acetate-C L(-1)) enhanced 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…Analytical Methods 2-CP and phenol concentrations were determined using a high performance liquid chromatography (PerkinElmer Series 200, USA) with a C-18 column (Phenomenex, USA) as previously described by Martínez-Gutiérrez et al [23]. The glucose concentration was determined using a YSI 2700 biochemical analyzer (YSI-2700 Select, USA) with a YSI membrane 2365.…”
Section: Batch Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical Methods 2-CP and phenol concentrations were determined using a high performance liquid chromatography (PerkinElmer Series 200, USA) with a C-18 column (Phenomenex, USA) as previously described by Martínez-Gutiérrez et al [23]. The glucose concentration was determined using a YSI 2700 biochemical analyzer (YSI-2700 Select, USA) with a YSI membrane 2365.…”
Section: Batch Assaysmentioning
confidence: 99%
“…There are also works which mention that the addition of electron donors (as cosubstrates) can decrease the toxic effects of chlorophenols, improving their consumption efficiency or removal rate [21][22][23]. Ye and Shen [24] observed that the degradation rate of 2-CP was at least 20 % higher in the presence of sucrose than in its absence.…”
mentioning
confidence: 98%
“…The compounds used as co-substrates include compounds of easy oxidation and compounds with a structure similar to chlorophenols. Regarding this, Martínez-Gutiérrez et al [73] evaluated the effects of phenol and acetate on the mineralization of 2-CP by a denitrifying sludge in batch assays. When phenol was used as a co-substrate, the specific rate of 2-CP consumption increased by 2.6 times, regarding to a control assay without co-substrate.…”
Section: Strategies For Improving the Consumption Of Chlorophenolsmentioning
confidence: 99%
“…The electrochemical process obtained in the present study might be coupled to a low-cost biological process where phenol could be totally mineralized. 23 Under the experimental conditions established in this study, the stoichiometric transformation of 2-CP into phenol was obtained, limiting the accumulation of others intermediates that could be toxic or inhibitory for the subsequent biological treatment. It has been reported that the limiting step in 2-CP mineralization by microbial processes is the reductive dechlorination of 2-CP to phenol, making very slow the overall process.…”
Section: H Adsmentioning
confidence: 99%